2(3x+4)=14-3(x-1)

Simple and best practice solution for 2(3x+4)=14-3(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x+4)=14-3(x-1) equation:


Simplifying
2(3x + 4) = 14 + -3(x + -1)

Reorder the terms:
2(4 + 3x) = 14 + -3(x + -1)
(4 * 2 + 3x * 2) = 14 + -3(x + -1)
(8 + 6x) = 14 + -3(x + -1)

Reorder the terms:
8 + 6x = 14 + -3(-1 + x)
8 + 6x = 14 + (-1 * -3 + x * -3)
8 + 6x = 14 + (3 + -3x)

Combine like terms: 14 + 3 = 17
8 + 6x = 17 + -3x

Solving
8 + 6x = 17 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
8 + 6x + 3x = 17 + -3x + 3x

Combine like terms: 6x + 3x = 9x
8 + 9x = 17 + -3x + 3x

Combine like terms: -3x + 3x = 0
8 + 9x = 17 + 0
8 + 9x = 17

Add '-8' to each side of the equation.
8 + -8 + 9x = 17 + -8

Combine like terms: 8 + -8 = 0
0 + 9x = 17 + -8
9x = 17 + -8

Combine like terms: 17 + -8 = 9
9x = 9

Divide each side by '9'.
x = 1

Simplifying
x = 1

See similar equations:

| X^2-13y^2=-1 | | 7a^2x1/9= | | 20+20*0+1= | | 2x-3=-(4x-9) | | -4(9-f)=36 | | .42-.03c=33.3-c | | 2n+2.9=5.5 | | .2(12)+.5x=.1(12+x) | | x^2+9y^2=2 | | d^2+8d-33=0 | | 2x+12=-2x-(8) | | x^3-5x^2-9x+45= | | r=6(b+a) | | 1.02(1.23)(7-x)=8 | | 100/x-10=15 | | =20x^4-100x^3-120x^2 | | 10(x+3)=40 | | 2x-3=-(4x-15) | | 100/x-10 | | 3=4x+103 | | 3b-2g+4b+7b= | | 9k^3x+36k^2x^2+36kx^3=0 | | 2x+12=-2x-8 | | .8(1+.5x)=.1(12+x) | | (7c+5)(3c-6)=0 | | 2(4x+2)=6x+2x+4 | | 6x+26=10x+18 | | -9(b^2+2b-3)+b(2b+5)+7= | | x^2-129x=0 | | 190+0.15x=322 | | -6(g+4)=12 | | -(8y+2)-(-7y-8)=-1 |

Equations solver categories